2014
DOI: 10.4161/auto.28374
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule-driven mitophagy-mediated NLRP3 inflammasome inhibition is responsible for the prevention of colitis-associated cancer

Abstract: (2014) Small molecule-driven mitophagy-mediated NLRP3 inflammasome inhibition is responsible for the prevention of colitisassociated cancer, Autophagy, 10:6,[972][973][974][975][976][977][978][979][980][981][982][983][984][985]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
156
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 235 publications
(175 citation statements)
references
References 60 publications
8
156
1
Order By: Relevance
“…Autophagy is a protector in tumor initiation and a booster in tumor progression, meanwhile, autophagy involves in inflammatory diseases by restricting inflammation and necrosis [57][58][59]. Recently, some reports have shown that novel therapies ameliorate CAC by regulating autophagy in tumor and immune cells [60][61][62]. As a vital autophagy inhibitor, whether HCQ modulates CAC through the autophagy pathway is unknown in this study.…”
Section: Discussionmentioning
confidence: 82%
“…Autophagy is a protector in tumor initiation and a booster in tumor progression, meanwhile, autophagy involves in inflammatory diseases by restricting inflammation and necrosis [57][58][59]. Recently, some reports have shown that novel therapies ameliorate CAC by regulating autophagy in tumor and immune cells [60][61][62]. As a vital autophagy inhibitor, whether HCQ modulates CAC through the autophagy pathway is unknown in this study.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, evidence indicates that dysfunction of mitophagy also promotes tumorigenesis and neoplastic progression (4,5,14). Guo et al reported that the induction of mitophagy in macrophages prevents the progression of colitis-associated cancer (22). Moreover, tumorigenesis and metastasis are also promoted by mitochondrial reactive oxygen species (ROS) (23).…”
Section: Biological Role Of Mitophagymentioning
confidence: 99%
“…A. paniculata has long been used as herbal medicine for the prevention and treatment of upper respiratory tract infection in Asian countries and in Scandinavia (14). Andrographolide has been shown to possess various biological activities, including antiviral (15), anticancer (13,16), anti-inflammatory (17,18) and antioxidative (15,19,20) activities.…”
mentioning
confidence: 99%